2022
DOI: 10.1186/s12884-022-05328-0
|View full text |Cite
|
Sign up to set email alerts
|

Afghan women’s empowerment and antenatal care utilization: a population-based cross-sectional study

Abstract: Background Although antenatal care (ANC) offers a unique opportunity to diagnose and prevent complications by mitigating modifiable risk, 38.2% of women did not complete any ANC visits in Afghanistan in 2015. Women empowerment is associated with increased use of ANC; however, there is no evidence of the effect of women empowerment on ANC in the country. Addressing this gap, we aimed to evaluate the association between women’s empowerment and ANC utilization based on the conceptual framework of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This finding was in line with the results of a systematic review undertaken in developing countries [ 50 ]. Other studies in Afghanistan have also highlighted the important role of husbands’ education in decision-making regarding seeking healthcare during pregnancy [ 21 , 51 ]. Consistent with previous studies, a husband with better education may have better understanding of the benefits of ANC services his wife would receive during ANC visits and such husbands are more likely to discuss with their spouses about issues related to women’s reproductive health and maternal health services [ 13 , 21 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding was in line with the results of a systematic review undertaken in developing countries [ 50 ]. Other studies in Afghanistan have also highlighted the important role of husbands’ education in decision-making regarding seeking healthcare during pregnancy [ 21 , 51 ]. Consistent with previous studies, a husband with better education may have better understanding of the benefits of ANC services his wife would receive during ANC visits and such husbands are more likely to discuss with their spouses about issues related to women’s reproductive health and maternal health services [ 13 , 21 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, cultural norms in Afghanistan, such as the expectations placed on new brides or first-time mothers, may also impact these associations. The status of a woman in her family and community, control over decision-making, traditional beliefs (about childbirth), and employment can also shape her access to and utilization of MNH services including ANC [ 21 ]. Although this finding is critical in understanding the factors influencing the utilization of ANC contents, some other studies have reported that higher parity decreases the likelihood of receiving higher ANC services by pregnant women [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations